Reduced order modelling of a flow around an airfoil with a changing angle of attack - Stankiewicz, W.; Morzyński, M.; Roszak, R.; Noack, B.R.; Tadmor, G. (Archives of Mechanics, 2008)
Model reduction based on Galerkin projection is a key technique used in feedback flow control. It significantly accelerates the flow computations, and thus it can be suitable for the aeroelastic simulations or, generally, in the flow analysis of changing configurations and boundaries. The present paper concerns the reduced-order Galerkin modelling of 2D flow around NACA-0012 airfoil, with angle of attack changing from α=30° to α=45°. It emphasizes the requirements of simplicity and accuracy of reduced order models (ROMs) used in control applications and discusses possible mode bases. Finally, it describes the constructed model, based on the modes resulting from Proper Orthogonal Decomposition (POD) and the novel technique of continuous mode interpolation. This method allows smooth transition between different operating and boundary conditions and allows the design of least-dimensional Galerkin model for control purposes.